Rethinking classifications and metrics for problematic smartphone use and dependence: Addressing the call for reassessment - Saqib Nawaz (Computers in Human Behavior Reports, 2023)
Despite numerous favourable consequences, excessive smartphone usage has been linked to behaviours that might be detrimental or unsettling, at least for some individuals. Accordingly, it becomes fundamental to re-evaluate the classifications and metrics used to identify problematic smartphone use and dependence (PSUD) due to their diverse negative impacts on users. This necessity is driven by factors such as the availability of numerous apps, changes in behaviour resulting from widespread adoption, and the recent impact of COVID-19. The distinction between smartphone dependence and other technological dependencies is a critical aspect explored in this narrative review. Additionally, it clarifies the difference between habitual and discretionary smartphone use. It is worth noting that increased reliance on smartphones has brought about both positive and negative outcomes. On one hand, it has facilitated better management of professional, familial, and social obligations. Conversely, it has led to adverse aspects, including inappropriate usage, excessive engagement, and ineffective use. However, assessing PSUD based exclusively on frequency and duration is an overly simplistic approach. It is essential to investigate the motivations behind smartphone engagement and differentiate between purposeful, productive, goal-oriented utilisation (effectual use) and impulsive, unnecessary interactions (ineffectual use). The terminologies associated with PSUD often complicate the precise definition, identification, and measurement of accompanying behaviours. Moreover, the ever-evolving technological landscape and shifting usage patterns combine these challenges. To address these complexities, this review suggests establishing a standardised framework that investigates the impact of technological shifts, evolving smartphone usage patterns, and behavioural effects. This review examines the causes, effects, and factors that contribute to PSUD, proposing the need to study strategies for effectively identifying and managing challenges related to PSUD.